Large-scale brain modes reorganize between infant sleep states and carry prognostic information for preterms - Anton Tokariev (Nature Portfolio, 2019)
Patterns of brain activity during sleep in early stages of life influence brain development and behavior. Here, the authors reveal cortical dynamics underpinning quiet and active sleep states in pre- and full-term infants, and their links to neurodevelopmental outcomes.